Strategy for Automation and Digitalization in Indonesian Aerospace Manufacturing - Ekawati, Dian; Yudoko, Gatot (Jurnal Bisnis dan Pemasaran Digital, 2024)
Purpose: Strategy formulation is part of organization design study to evaluate decision thoroughly, then enable organization to achieve company goal. This study aims to formulate strategy of automation and digitalization for PT XYZ, to be ready for welcoming future growth of demand by maintain competitive cost within the same industry. Method: The study collects primary data from focus group discussion with selected participant of PT XYZ, located in Bandung, Indonesia, with participant selection based on information rich person reference. Data collection and analysis utilize qualitative and quantitative approach, and utilize three steps of strategy formulation (input stage, matching stage and decision stage). Results: Strategy formulation steps as per theory, applicable to finalize strategy to support industry 4.0 transformation at PT XYZ. Combine steps with latest internal and external factor analysis method, such as PESTLE, VRIO, Porter Value Chain analysis, and QSPM, help broaden the perspective of the participant during discussion. The study resulted eight strategies, which then simplified by data reduction approach to be four. Conclusions: The study successfully formulates PT XYZ's digital transformation strategy for Industry 4.0 by integrating comprehensive strategic tools such as PESTLE, Value Chain Analysis, VRIO, SWOT, TOWS, and QSPM. Strategy execution is prioritized in three phases: establishing an organizational hierarchy aligned with internal capabilities, adapting appropriate technologies to support human functions, and enhancing local and intercompany networks. Limitations: This study is limited by its qualitative reliance on focus group discussions, which may be influenced by participant bias and lack real-time implementation feedback. Contributions: By conducting this study, author expect it will prove the practical implementation of strategy formulation in industry 4.0 transformation for aerospace industry in Indonesia and Asia.